2017
DOI: 10.1111/jzs.12176
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus phylogeny and species delimitation within the genusGlauconycteris(Chiroptera, Vespertilionidae), with the description of a new bat species from the Tshopo Province of the Democratic Republic of the Congo

Abstract: The genus Glauconycteris Dobson, 1875 currently contains 12 species of butterfly bats, all endemic to sub-Saharan Africa. Most species are rarely recorded, with half of the species known from less than six geographic localities. The taxonomic status of several species remains problematic. Here, we studied the systematics of butterfly bats using both morphological and molecular approaches. We examined 45 adult specimens for external anatomy and skull morphology, and investigated the phylogeny of Glauconycteris … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In most cases, such patterns are attributable to adaptive introgression of mtDNA, demographic disparities, and sex-biased asymmetries; in some cases they found evidence for hybrid zone movement or human agency. Discordant patterns of variation between mitochondrial and nuclear DNA have been reported in at least six other families of bats (Nesi et al 2011;Furman et al 2014;Naidoo et al 2016;Hassanin et al 2018;Demos et al 2019a;Gürün et al 2019). Gürün et al (2019) implicated the role of sex-biased dispersal in causing such discordance, male dispersal spreading nuclear variation farther and faster than the movement of mitochondria.…”
Section: Species Limitsmentioning
confidence: 73%
“…In most cases, such patterns are attributable to adaptive introgression of mtDNA, demographic disparities, and sex-biased asymmetries; in some cases they found evidence for hybrid zone movement or human agency. Discordant patterns of variation between mitochondrial and nuclear DNA have been reported in at least six other families of bats (Nesi et al 2011;Furman et al 2014;Naidoo et al 2016;Hassanin et al 2018;Demos et al 2019a;Gürün et al 2019). Gürün et al (2019) implicated the role of sex-biased dispersal in causing such discordance, male dispersal spreading nuclear variation farther and faster than the movement of mitochondria.…”
Section: Species Limitsmentioning
confidence: 73%
“…As if to confirm the previous statement, after the manuscript for this paper was submitted, Ing et al (2016) and Hassanin et al (2017) reported on ten additional specimens from Mbiye island and the Yoko Forest Reserve (00°17′ N, 25°17′ E). Hassanin et al (2017) also described a new species of Glauconycteris, which is not covered in the current paper.…”
mentioning
confidence: 77%
“…Hassanin et al (2017) also described a new species of Glauconycteris, which is not covered in the current paper.…”
mentioning
confidence: 99%
“…1). Some mito-nuclear conflicts can be simply explained by recent hybridization between sympatric or parapatric taxa (species or subspecies), resulting in the transfer of the mitochondrial genome from one taxa to the other, a process referred to as mitochondrial introgression [6–11].…”
Section: Discussionmentioning
confidence: 99%